Communicating quality audit indicators for inbound tourism: a qualitative insight from Malaysian travel agencies - Saad, Mazni; Mohamad Ali, Afiza; Ismail, Zahid; Mohd Arop, Nor Hafizah; Baharudin, Noor Zaleha (Eurasia Business and Economics Society, 2019)
Quality assurance is fundamental to all business activities in the tourism sector as it is advantageous to market recognition and competitiveness. Awareness of the importance of quality assurance certifications is already in place in Malaysia however it is still under-researched. Thus, this study aims to investigate how local travel agency operators perceive suitable levels of quality audit indicators for inbound travel agencies. A semi-structured interview was conducted to explore the views and experiences of key industry players from five travel agencies involved in both inbound and outbound tourism businesses in the country. A content analysis of data acknowledged the industry's increased awareness of quality service delivery and the importance of rationalising key quality audit indicators in assuring the lifelong survival of inbound Malaysian travel agencies. Also found was the need for systematic monitoring of the inbound travel agency's certification plan that continually reflects the demands of the clientèle and uplifts national productivity as outlined in the initiatives undertaken by the Tourism Productivity Nexus, an industry-led establishment under the Malaysia Productivity Blueprint 2016-2020. The study finally outlines specific entrepreneurial strategies that will enhance productivity operations at the enterprise level.